Efektivitas Pemberian Hormon Tiroksin (T4) terhadap Pertumbuhan Ikan Pawas (Osteochillus hasselti CV) - Susanti, Nelvia Mai; Sukendi, Sukendi; Syafriadiman, Syafriadiman (Fakultas Perikanan dan Kelautan Universitas Riau, 2016)
Thyroxine hormones (T4) is a technology that is used to stimulate fish growth. This hormone is produced by the thyroid gland and functioning in general metabolism and growth. This study was conducted from May-July 2016 in Hatchery and Breeding Laboratory, Department of Aquaculture, Fisheries and Marine Sciences Faculty, Riau University. This study was aimed to analyze the effectiveness of the thyroxine hormone (T4) at different dosages to the growth of Pawas fish (Osteochillus hasselti CV), and reared with different density. This study used a complete randomized design with two factors (densities and dosages of hormones) and 3 repetitions. The densities that used were 20, 30 and 40 fish / cage. The hormone dosages given in this study were 2, 4, and 6 mg/kg. The results showed that the density 20 fish/cage is the best density in Pawas culture where the best result of the growth parameters obtained. Addition of thyroxine at a dosage of 6 mg / kg of feed provided the best results on the absolute weight growth (5:12 ± 1.70 g), daily growth rate (2.64 ± 12:47%), protein retention (58.76 ± 8:34%) and the levels of muscle glycogen (4:54 ± 0.20). Addition of thyroxine at a dosage of 4 mg/kg feed gave the best results in the absolute long growth (4.72± 0.89 cm), feed conversion ratio (1:44 ± 0.57), fat retention (108.50 ± 12:47%) and the levels of liver glycogen (6:12 ± 2.60).